Efeitos da prática de Yoga na memória e em parâmetros psicológicos e fisiológicos de indivíduos saudáveis - Rocha, Kliger Kissinger Fernandes (2011)
Techniques of mind & body control seem to benefit human organism in general and cognition in particular, because they involve a mindfulness practice. However, there is still a scarcity of studies with well-controlled methods to investigate the possible effects of Yoga practice. In this study, we investigated the effects of regular Yoga practice, based on Yoga postures (asanas), breathing techniques, and meditation exercises, on memory and physiologic and psychological parameters related to quality of life. There were significant improvements on performance tasks of short term memory and long term memory. We also observed significant beneficial effects on psychological and physiological parameters such as mood, anxiety, depression, stress, and modulation of the autonomic nervous system in Yoga practitioners group compared to the conventional physical exercises group. The results suggest the possible influences of stress, emotional state and mental training on cognitive effects of yoga practice. Our results support the indication of practice of Yoga for the treatment or prevention of stress, psychological disorders and their possible cognitive consequences